The chemical composition of the ethanolic extract from Chromolaena odorata leaves correlates with the cytotoxicity exhibited against colorectal and breast cancer cell lines - Hanifah Yusuf; Fauzul Husna; Basri A. Gani (GarVal Editorial Ltda., 2021)
Context: Colorectal and breast cancer are of particular cellular preventive concern. WIDR cells are an indicator of colorectal cancer development, while HTB and 4T1 cells are involved in breast cancer. The Chromolaena odorata was reported to interfere with the growth of the three cancer cells. Aims: To evaluate the bioactivity of C. odorata against the cytotoxicity of colorectal and breast cancer cells. Methods: Ethanol extract of C. odorata leaves was examined to find chemical compounds by GC-MS, quality of antioxidants by DPPH assay, and antioxidants quantity by flavonoids and phenolic assay, whereas ionic values were evaluated by the multi-tester meter also cytotoxicity on the WiDr, HTB, and 4T1 cancer cells by MTT assay. Results: C. odorata contained six antioxidant compounds with quality above 80%. Alpha-amyrin has the most retention time of 38.112 min. The C.odorata had an antioxidant rate (IC50) higher than vitamin C. Total flavonoids (72%) higher than total phenolic (28%), and both have a significant impact on the WiDr, HTB, and 4T1 cancer cells (p<0.05). The value of ionic dissolved oxygen, conductivity, and total dissolved solids was 33%, respectively (p>0.05).The C. odorata had a higher cytotoxicity effect on the 4TI and HTB cells in breast cancer than WiDr cancer cells in colorectal cancer. Conclusions: The C. odorata has significant antioxidant quality and quantity with a stable ionic value also has a cytotoxic effect on the WIDR, HTB, and 4T1 cancer cells.